1963
DOI: 10.1111/j.1151-2916.1963.tb11774.x
|View full text |Cite
|
Sign up to set email alerts
|

Sintering of Zinc Oxide

Abstract: Sintering of Zinc Oxide 449 oxygen enters the lattice substitutionally. According to a theory by Lidiard,6 substitutional impurities diffuse in ionic crystals by forming complexes with vacancies on the same sublattice. One may therefore expect oxygen to diffuse into CaF2 by forming complexes with fluorine vacancies.One may further question whether the penetration is limited by the extrinsic or intrinsic diffusion rate of oxygen into CaF2 On the basis of Lidiard's theory, the activation energy for intrinsic dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

1966
1966
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 4 publications
3
13
0
Order By: Relevance
“…3a -d) and also reported in the literature [27,30,31], the addition of B 2 O 3 significantly promoted the grain growth of ZnO and resulted in the uniform microstructure due to the low melting temperature of B 2 O 3 [32]. As mentioned previously, the grain growth exponent value (n) of 3 was consistently observed for pure ZnO [2,[27][28][29]. According to Hng and Halim, the small value of n obtained for ZnO -1 mol %V 2 O 5 system indicated that the grain growth was much faster than for pure ZnO [33].…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…3a -d) and also reported in the literature [27,30,31], the addition of B 2 O 3 significantly promoted the grain growth of ZnO and resulted in the uniform microstructure due to the low melting temperature of B 2 O 3 [32]. As mentioned previously, the grain growth exponent value (n) of 3 was consistently observed for pure ZnO [2,[27][28][29]. According to Hng and Halim, the small value of n obtained for ZnO -1 mol %V 2 O 5 system indicated that the grain growth was much faster than for pure ZnO [33].…”
Section: Resultssupporting
confidence: 54%
“…Senda and Bradt calculated the activation energy as 224±16 kJ/mol for sintering a pure ZnO system [2]. On the other hand, Norris and Parravano measured the early stages of neck growth of ZnO spheres from 1050 to 1250°C and found much larger activation energy of 440 to 461 kJ/mol as well as smaller grain sizes [28]. This difference can probably be attributed to the processing conditions and to the raw material properties, such as powder particle morphology, particle size distribution or impurities contained within the powder, creating grainboundary drag, decreasing grain-boundary mobility, thus, the grain size, by slowing the rate of the grain growth [2].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ZnO sintering mechanisms were extensively studied in the 1960s [12][13][14]; different groups conducted sintering experiments in air and concluded that the densification process of pure submicronic ZnO powders is essentially completed in about 1 h even at a low temperature of 900 • C, with a relative density of around 98% [15]. However, grain growth was important, leading to final grain sizes between 3-50 µm, depending on sintering time and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The grain size of ZnO sintered under nitrogen was smaller (about 10 μm) than that sintered under air (above 20 μm). Several previous studies have revealed that the zinc diffusion is responsible for the solid-state sintering (Norris et al 1963;Gupta et al 1968;Lee et al 1959) since the oxygen diffusion coefficient is several orders of magnitude slower than that of zinc (Gupta et al 1968). The oxygen from the atmosphere can diffuse faster along the grain boundaries at high temperatures and react with zinc during sintering (Gupta et al 1968).…”
Section: Resultsmentioning
confidence: 99%